Análise de eficiência operacional e financeira nas empresas de transporte coletivo urbano por ônibus na cidade de São Paulo através do método de análise por envoltória de dados no ano de 2011 - Hernandes Júnior, Urbano Bueno (2013)
This research approaches the application of DEA method (Data Envelopment Analysis) to the operational and financial performance of companies of local public transport of passengers by bus in the city of São Paulo in the year of 2011, at the same time in which it presents theoretical referential about benchmarking, about the DEA method, its concepts, methodology, and some applications in transport, and about the measurement of economic and financial performance of those companies. The methodology of this research consists in the identification of a DEA model to be applied to both the measurement of the operational efficiency and the financial one, obtaining a score of efficiency to each of them, afterward for applying Pearson’s Correlation and for verifying the level of correlation between these efficiencies. The data used in this study were verified from (i) technical and operational reports of São Paulo Transporte S/A, and from (ii) account statements of each firm, all of them from 2010 and 2011. The results attained show that there is a larger dispersion in the score of financial efficiency than in the operational one. It wasn´t possible to apply Regression Analysis. The correlational level was moderate, suggesting that new researches may be conducted for detecting other motives that complement the relationship between operational efficiency and financial one in public transportation by bus in the city of São Paulo.